2 1) y = (x - ) + 3 X - 2 23 E) 2 23 B. Write the indicated letter of the quadratic function in the form y ax2 + bx + C , into the space provided that corresponds to its equivalent standard form. I) y = x2 – 2x - 3 2) y = 3 (x + 2)2 -- 1 y S y = 2x2 + 5x - 3 3) y = (x - 1)2 - 16 y = 3x2 + 6x + 4). y = 2 (x + 1)2 - 2 A) y = 3x2 + 12x + = 5) y = (x - 1)2 - 4 N) y = x2 - 36 y ( T) y = x2 – 2x – 15 7) y = (x – 3)2 + 5 7 F) y = x2 - 6x +14 8) y = -2 (x - 3)2 + 1 M) y = x2 – x +? - 9) y = (x - 0)2 – 36 U) y = -2x2 + 12x – 17 H) y = 2x2 + 4x 2 2 49 6) y = 2(x + - 8 4 1 2 3 4 5 LO 6 7 8 9